Asymptomatic anal extrusion of a migrated ventriculoperitoneal shunt: Case report and literature review (Nepal Journal of Neuroscience, 2026)
Background: Ventriculoperitoneal (VP) shunting is the most common surgical treatment for hydrocephalus; however, it is associated with various complications. Bowel perforation with transanal extrusion of the distal catheter is a rare but serious complication, which may remain asymptomatic and lead to life-threatening infections if not recognized early.Case Presentation: We report a case of a 2-year-old female child with congenital hydrocephalus who presented with asymptomatic extrusion of a VP shunt through the anus. The child had undergone a right-sided VP shunt placement 10 months prior, followed by revision for hardware failure. On evaluation, she was clinically stable with no signs of peritonitis or meningitis. Imaging confirmed migration of the distal catheter into the bowel. Surgical exploration revealed perforation of the transverse colon. The distal catheter was removed, bowel perforation was repaired, and the shunt was revised. The patient later developed wound discharge and abnormal movements, requiring shunt externalization and further CSF monitoring. After ensuring sterile CSF, the shunt was revised on the contralateral side. The child showed good recovery and remained asymptomatic at 3-month follow-up.Conclusion: Transanal extrusion of a VP shunt is a rare but important complication that may present without abdominal symptoms. Early diagnosis and timely management are crucial to prevent serious infections and improve outcomes. Regular follow-up and high clinical suspicion are essential, especially in pediatric patients.